Effect of depolymerized block skim rubber (BSR) on the physical properties of modified asphalt - Arief Ramadhan; Adi Cifriadi; Henry Prastanto; Norma Arisanti Kinasih (Majalah Kulit, Karet, dan Plastik, 2018)
The asphalt pavement susceptibility was influenced by traffic load and temperature. Therefore, modified asphalt has been done to improve the asphalt performance. Depolymerized block skim rubber (BSR) was used as asphalt modifier. BSR is a low quality crumb rubber, which made from skim (byproduct of creamed latex). This investigation aims to determine effect of depolymerization of BSR on the physical performance of modified asphalt. Initially, BSR was depolymerized by mechanical action (mastication) with different time of 8, 16, and 24 min. Then, the asphalt modifier, depolymerized BSR was added to asphalt with different ratio 3, 5, 7%. The softening point and mixing time of asphalt were compared with modified asphalt. The performance of modified asphalt showed that asphalt modifiers increased the softening point and mixing time of asphalt. Maximum softening point reached 54.30C by 7% BSR (16 min. of mastication time). The modified asphalt had 25.70C softening point higher than asphalt. It was conclude that depolymerized BSR can increase the performance of asphalt (softening point), although increase the mixing time of it. Moreover, it could give alternative to reduce cost of modified asphalt pavement making.